On the Cryptops subgenus Trichocryptops Verhoeff, 1937, with a discussion of the problems of differentiating Cryptops species (Chilopoda: Scolopendromorpha: Cryptopidae) - Lewis, John G. E. (Zootaxa, 2016)
Three putative species comprising Verhoeff’s Cryptops subgenus Trichocryptops are here reviewed. There is little justification for the retention of the subgenus and the three species previously assigned to it are here placed in synonymy with the subgenus Cryptops. Cryptops (T.) malaccanus Verhoeff, 1937, closely resembles Nepalese C. doriae Pocock, 1891, and it is proposed that it be regarded as its junior subjective synonym. Cryptops doriae, as presently understood, is widely distributed and quite variable. Cryptops (T.) brachyraphe Attems, 1934, and C. (T.) iucundus Würmli, 1972, are very similar but bearing in mind the present paucity of material, they are here retained as separate species. The possible characters distinguishing populations of C. doriae, C. nepalensis Lewis, 1999 and the three “Trichocryptops” species and C. niuensis Chamberlin, 1920, are reviewed. The current situation is far from satisfactory. Individual variation, possible ontogenetic changes, a relative paucity of morphological characters and small numbers of individuals render decisions as to the status of some Cryptops specimens problematical and subjective.